유산소 운동에 따른 생물광자의 반응 - 서동일(Dong Il Seo); 전태원(Tae Won Jun); 소위영(Wi Young So); 김지석(Ji Seok Kim); 김희태(Hee Tae Kim); 송욱(Wook Song) (한국체육측정평가학회지, 2010)
본 연구의 목적은 유산소운동으로 인한 인체의 생물광자 방출에 대한 결과를 고찰하는데 있다. 본 연구에서는 건강한 남자 대학생 15명을 대상으로 유산소운동을 실시하도록 하였고, 운동중 심박수, 산소섭취량, 생물광자 방출의 변화를 살펴 보았다. 생물광자의 방출량은 암실에서 Photon Multiplier Tube(PMT)를 사용하여 측정하였고, 생물광자측정 일주일 후 심박수와 산소소비량의 측정을 생물광자 측정시와 같은 운동방법으로 실시하였다. 본 연구의 결과 유산소 운동 중 생물광자의 방출량이 통계적으로 유의하게 감소하였다(p<.05). 이러한 결과는 적절한 강도의 유산소 운동은 체내의 산소소비량의 증가와 함께 산화적 스트레스의 감소를 가져오기 때문에 생물광자 방출량의 감소 가능성을 제시 한 것이라 사료된다. The purpose of this study was to examine biophoton emission of the human body during aerobic exercise. In this study, 15 Healthy college male students who exercised regularly and were not claustrophobic nor dark-phobic were participated. The difference in heart rate, VO2, and biophoton emission was monitored carefully during aerobic excercise(cycling). To measure the amount of biophoton emission, PMT(photo multiplier tube) were used in the dark room. In order to measure the VO2 and heart rate, the identical protocol was conducted a week later. During aerobic exercise, VO2 and heart rate was increased significantly(p<0.01). However biophoton emission was significantly decreased(p<0.05). In conclusion, the biophoton emission decrease can be explained that subjects of the experiment were people who trained regularly, which enable them to have little effect of ROS. Additionally, more research is needed to understand the mechanism of biophoton emission. KCI Citation Count: 0